(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
In a global context where suffering is often reduced to fleeting headlines and the voice of the oppressed is increasingly marginalized, Gaza Theory: Writing from Beneath the Rubble emerges as a contemporary literary and critical framework for reading texts produced under siege, occupation, and destruction. While rooted in the Palestinian experience, the theory transcends geography, proposing a universal lens through which literature written from within human catastrophe can be interpreted. Gaza, in this theory, is not merely a location—it is a symbolic and existential condition. The theory introduces key concepts such as "emergency language," "the besieged self," and "explosive realism," redefining aesthetics not as ornamentation, but as the act of persisting in language amid collapse. It affirms that resistance literature is not propaganda but a profound human and artistic expression of survival, identity, and dignity. The theory also deliberately avoids rigid methodologies, leaving space for interpretive multiplicity and encouraging readers and scholars to engage literature from within lived experience and ethical responsibility.